CONTESTATION BEHIND TOLERANCE: BETWEEN COMPETITION AND TOLERANCE IN THE DISCOURSE OF MULTICULTURALISM IN SALATIGA - Mukti Ali; M. Ali Sofyan; Rr. Wuri Arenggoasih (Universitas Islam Negeri Ar-Raniry, 2020)
Tolerance must be close to pluralism and multiculturalism which is not a new thing in academic studies. Many studies and research generalize about respect and appreciation for the diversity of ethnicity, religion, language and other cultures. For Javanese people who tend to be homogeneous in ethnicity but not too many long conflicts arise. Truth, the proof, One of the results of research in Salatiga which is one of the student cities in Central Java received the title of the second most tolerant city in Indonesia in 2018. But behind the award, there was contestation in the fields of education and religion. This paper will look again at tolerance in the Salatiga community after the award was obtained. Besides that, it also discussed competition in academia at IAIN Salatiga and Satya Wacana Kristen University (UKSW). Both educational institutions are based on religion, in which multiculturalism. Both educational institutions are based on religion, which is multicultural so that it impacts on the contestation of institutional policies, facilities and theological expansion. The results of this study are obtained from social phenomena which are understood by the phenomenology paradigm from reality understood in consciousness. In addition, during activities in Salatiga, there were also some social realities about tolerance and competition in the field of education. Finally, tolerance that has gone well does not mean without contestation. Contestation in this case is one of the social and cultural dynamics. Even to achieve social integration, sometimes conflict with good management is needed. This means that contestation or conflict does not always lead to division, but rather one of the paths to integration.